The anxieties of medical students related to clinical training - SARIKAYA, ÖZLEM (WILEY, 2006)
High levels of anxiety and stress during medical education may have negative effects on students' learning and may also influence students' performance, decision-making and caring capabilities. This study aims to compare the anxieties of clerkships of two medical schools that apply two different preclinical curricula; one is problem-based and the other is integrated. Dokuz Eylul University School of Medicine (DEUSM) has the basic clinical and communication skills education by the first year of medical education. However, the students of Marmara University School of Medicine (MUSM) had not any preclinical training about these issues at the time we performed this study. In order to evaluate the perceived anxiety, we used a questionnaire which comprises 39 issues presented as 4-point Likert-type scales. Eighty-six clerkships from MUSM and 115 clerkships from DEUSM participated in the study. According to the students of both of the schools, fear of making mistakes that could harm the patients was at the top of the list of sources of anxiety. The students of MUSM have additional anxieties related to the core clinical skills such as suturing patients, taking blood from patients and giving injections. On the other hand, the students of DEUSM have anxieties mostly related to difficult issues in communication such as breaking bad news. The study has revealed that medical students might have anxiety related to the clinical practice in the beginning of their clerkships. It was also shown that sources of anxiety may vary among students exposed to different preclinical curricula and different educational environment. If basic clinical and communication skills courses are integrated in preclinical curriculum, the students would meet some clinical task in the early year and would be orientated through clinical period.
Keywords: undergraduate medical education; clinical skills; communication skills; anxiety; stress; STRESS; EDUCATION